Analisis Efisiensi Pengelolaan Zakat dengan Metode Super Efisiensi Data Envelopment Analysis (DEA) pada LAZ Mizan Amanah - Nadhifah Salsabila Firdaus; Radia Purbayati; Iwan Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
Zakat Organizations have important roles in creating the goals of Zakat Management as stated in Law No. 23 of year 2011, namely to increase the effectiveness and efficiency zakat management for improving social welfare and poverty alleviation. The goal of this research is to analyze the efficiency of zakat management in LAZ Mizan Amanah 2012-2019 period. The research uses descriptive quantitative and qualitative methods with a case study approach. Meanwhile, the analysis technique used is Super Efficiency Data Envelopment Analysis (DEA). The input variables used are personnel costs, socialization costs, and operational costs. Whereas the output variables are the amount of zakat received and the amount of zakat distribution. The results showed that 5 (five) of the 8 (eight) DMU observed were efficient. The first rank with the highest efficiency value was obtained by DMU Mizan 2015. The inefficiency that occurs in DMU is caused by high personnel costs and operational costs, as well as the nonoptimal zakat’s accumulation and distribution.